Exploring National Trends in Bladder-Related Urological Procedures: A Nationwide Population-Based Cohort Study - Hyosang Kwon; Wonjong Yang; Sangyong Park; Heesub Lee; Jong Keun Kim; Jun Hyun Han (Urogenital Tract Infection, 2023)
Purpose This study examined the epidemiological trends of bladder-related urological procedures in South Korea from 2009 to 2021. Materials and Methods The data were obtained from the Health Insurance Review and Assessment Service (HIRA) database, encompassing various bladder-related urological procedures. The frequencies and trends were analyzed using statistical methods. Results Uroflowmetry, cystoscopy, prostate biopsy, and urethral dilation showed a positive trend, while prostate massage exhibited a negative trend. The 72-hour voiding function test, which started in 2017, also demonstrated a positive trend in frequency. A urodynamic study and mid-urethral sling operation exhibited an overall decreasing trend. Bladder-indwelling catheter, Nelaton catheterization, and cystostomy catheter change showed increasing trends, while suprapubic cystostomy showed a decreasing trend. Conclusions This 12-year analysis provided valuable insights into the epidemiological patterns and utilization of bladder-related urological procedures in South Korea. These trends highlight the evolving landscape of diagnostic and therapeutic approaches in bladder-related conditions and the importance of interdisciplinary collaboration between urology and other medical departments. The results highlight the need for optimizing catheter-related care protocols, resource allocation, and continued monitoring of practices across healthcare settings.